(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Lantanophaga pusillidactylus (Walker, 1864) has been found in urban areas; this species is recorded for the first time in Italy (Sicily); it feeds on Lantana camara L. and L. montevidensis (K. Spreng.) Briq